2017
DOI: 10.1097/md.0000000000006344
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of subchondral bone changes of the hand in rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic and systemic inflammatory disorder. Conventional radiography, a widely available and cost-effective examination method, remains the standard of reference for the detection and quantification of joint involvement in RA. Fractal dimension (FD) of the trabecular bone structure has been proven to correlate with the bone's physical properties. The present study was designed to use fractal analysis to validate radiograph changes in the hand of RA patients.This study retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Among the parameters, we used the bone structure value (BSV) to analyze changes in the microstructure of the tibial subchondral bone after PN-filler treatment. According to previous studies on radiocarpal and knee joints, BSV is considered as a maximum-likelihood estimator of OA [ 30 , 31 , 32 ]. The BSV algorithm analyzes the self-similarity (uniformity) in the fractal dimension of the bone support structures based on the gray values of an X-ray image.…”
Section: Methodsmentioning
confidence: 99%
“…Among the parameters, we used the bone structure value (BSV) to analyze changes in the microstructure of the tibial subchondral bone after PN-filler treatment. According to previous studies on radiocarpal and knee joints, BSV is considered as a maximum-likelihood estimator of OA [ 30 , 31 , 32 ]. The BSV algorithm analyzes the self-similarity (uniformity) in the fractal dimension of the bone support structures based on the gray values of an X-ray image.…”
Section: Methodsmentioning
confidence: 99%
“…Information about the 3D structure of the bone can be obtained through two-dimensional images, and fractal analysis enables detection of details that may be missed on radiographs [ 4 , 13 , 20 ]. Changes in the trabecular bone pattern have been demonstrated in several studies using fractal analysis [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, fractal-based analysis applied to trabecular bone of calcaneus radiographs has been shown to discriminate between patients with prevalent vertebral fractures from such without, and that the discriminative power of fractal analysis may even be superior to that provided by BMD measurement [ 11 , 12 ]. In addition, it has been demonstrated that if applied to conventional radiographs of subchondral bone of the proximal tibia in patients with osteoarthritis, fractal-based analysis may provide reliable information on osteoarthritis progress, facilitating quantification of the severity and classification of this disease [ 13 , 14 ]; and finally, it has been demonstrated recently that fractal-based image analysis, similar to the one used in the prevailing study, can be used to quantify the radiographic changes of subchondral bone in rheumatoid arthritis hands [ 15 ].…”
Section: Introductionmentioning
confidence: 99%